(untitled) (Texas Journal of Medical Science, 2022)
The place of traditional sulfonylurea (SM) drugs that stimulate insulin secretion began to be occupied by incretin drugs , primarily dipeptidyl peptidase-4 (iDPP-4) inhibitors, due to their unique physiological glucose-dependent effect on the secretion of insulin and glucagon, allowing effective control of diabetes mellitus (DM) . ) 2 types without significant side effects. Drugs of the DPP-4 class are recommended for use at all stages of the development of diabetes, starting from the onset, both in monotherapy and in combination with oral hypoglycemic drugs (PSP) and insulin. Cardiovascular safety, the ability to take in the late stages of chronic kidney disease (CKD), a neutral effect on body weight, ease of use are their undeniable advantages. The combination of iDPP-4 (for example, vildagliptin ) with metformin is the most popular, covers the vast majority of pathophysiological defects in type 2 diabetes, is available in a fixed form (for example, Galvus Met). More than 10 years of experience in clinical practice with drugs of the DPP-4 class (for example, Galvus) suggests that their main clinical effects have been finally identified, they can be systematized and the established advantages and disadvantages in the management of type 2 diabetes can be discussed.